2004
DOI: 10.1111/j.1471-4159.2004.02832.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activation of Akt and extracellular‐regulated kinase pathways by simultaneous occupancy of Gq‐coupled 5‐HT2A receptors and Gs‐coupled 5‐HT7A receptors in PC12 cells

Abstract: The most commonly prescribed antidepressants, the serotonin (5-HT) selective reuptake inhibitors, increase 5-HT without targeting specific receptors. Yet, little is known about the interaction of multiple receptor subtypes expressed by individual neurons. Specifically, the effect of increases in cAMP induced by G s -coupled 5-HT receptor subtypes on the signaling pathways modulated by other receptor subtypes has not been studied. We have, therefore, examined the activation of the extracellular-regulated kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 39 publications
(82 reference statements)
3
48
0
Order By: Relevance
“…The low levels of ERK1/2 phosphorylation may explain why other studies found no effect of this Epac-selective cAMP analog on ERK1/2 activity in PC12 cells (Enserink et al, 2002;JohnsonFarley et al, 2005). In agreement with a role of Epac in cAMP-induced ERK1/2 activation in PC12 cells, overexpression of Epac1 enhances ERK1/2 activation upon stimulation of G s -coupled 5-HT 7A receptors in these cells (Johnson-Farley et al, 2005).…”
Section: )supporting
confidence: 54%
“…The low levels of ERK1/2 phosphorylation may explain why other studies found no effect of this Epac-selective cAMP analog on ERK1/2 activity in PC12 cells (Enserink et al, 2002;JohnsonFarley et al, 2005). In agreement with a role of Epac in cAMP-induced ERK1/2 activation in PC12 cells, overexpression of Epac1 enhances ERK1/2 activation upon stimulation of G s -coupled 5-HT 7A receptors in these cells (Johnson-Farley et al, 2005).…”
Section: )supporting
confidence: 54%
“…The PKA inhibitor, H89, did not have an effect on GLP-1 protective action due, probably, to a different system (ex vivo culture), that used a culture medium with several growth factors contained in the fetal calf serum, and the possibility of cAMP induced ERK1/2 activation in a PKA-independent manner. In this sense, the role of cAMP-regulated guanine nucleotide exchange factor (Epac) in GLP-1 receptor-mediated signal transduction in b cells, and Epac-dependent, PKA-independent ERK1/2 activation in response to cAMP has been described (Busca et al 2000, Lin et al 2003, Holz 2004, Johnson-Farley et al 2005, Fang & Olah 2007. On the other hand, treatment with PD98059, which blocks ERK1/2 pathway by inhibiting MAP kinase (MEK), abrogates the effect of GLP-1 on cytokine-treated cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Although PKA is a main downstream target of cAMP signaling (Beebe 1994;Nguyen and Woo 2003), PKA-independent activation of ERK and mTOR signaling cascades has been demonstrated. For example, activation of 5-HT7A receptors results in stimulation of cAMP-regulated guanine exchange factors (cAMPGEFs) (Johnson-Farley et al 2005). Thus, direct coupling of cAMP to intracellular signaling pathways, such as ERK, via cAMP-GEFs, may occur downstream of the ␤-AR receptor to enhance the maintenance of LTP.…”
Section: Discussionmentioning
confidence: 99%